Identification of Eggs of Intestinal Nematodes of the Soil Transmitted Helminths Group on the Soil of the Sindupraja River - Pipin Supenah (Postgraduate, University of Mataram, 2025)
This research aims to determine the presence of Soil Transmitted Helminths group intestinal nematode worm eggs, to determine the type of Soil Transmitted Helminths egg species and to determine the percentage of soil samples that are positively contaminated with Soil Transmitted Helminths eggs. The research method used in this research is a descriptive survey method. This research design uses Belt Transect-Quadrat sampling and Hand Sorting methods. The sampling technique used is probability sampling, namely in the form of Stratified Random Sampling. The data collection technique used is observation. The river bank soil is then put into a labeled container and then tested in the laboratory using the flotation method using saturated Nacl. After the data is collected, the data is processed using descriptive statistical analysis. The results of the above examination showed that 12 soil samples were positively contaminated with the eggs of intestinal nematode worms of the Soil Transmitted Helminths group. The condition of the river soil in the area is that the soil is generally quite contaminated with the eggs of intestinal Nematode worms of the Soil Transmitted Helminths group, including the eggs of Ascaris lumbricoides, Trichuris trichiura, Hook worm. (Hookworm), that is, there were 33.3 (%) soil samples contaminated with intestinal nematode eggs of the Soil Transmitted Helminths group.